(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The aim of this research is to study the behavior of fiber epoxy composite curve pipe under internal pressure and bending moment. The specimens made from woven roving (Mat) fiber glass pipes and epoxy composite with 50% volume fraction are used to manufacturing curved pipe. The experimental work included manufacturing pipe specimens by vacuum bag technique. Pipe specimens were having 100mm inner diameter, 450 mm length of curvature center line of curve pipe with (43 degree) and two wall thickness are 4 and 3 mm. The test rig was designed and performed to study the effect of internal pressure and bending moment on the composite pipes. Also, the tensile test of the samples was done. The analytical expression solution has been accomplished to determine the strain, stress, for hoop and longitudinal direction. It is evident that the hoop stress for woven roving fiber composite pipe was more than longitudinal stress by almost (14%). The maximum internal pressure in the case of internal pressure only was more than compared to the combined internal pressure with bending moment by almost (115%). The most dangerous region is found in the inner arc of the curved pipe (intrude) area.